2013
DOI: 10.1063/1.4816041
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational solvatochromism: Towards systematic approach to modeling solvation phenomena

Abstract: Vibrational solvatochromic frequency shift of IR probe is an effect of interaction between local electric field and IR probe in condensed phases. Despite prolonged efforts to develop empirical maps for vibrational frequency shifts and transition dipoles of IR probes, a systematic approach to ab initio calculation of vibrational solvatochromic charges and multipoles has not been developed. Here, we report on density functional theory (DFT) calculations of N-methylacetamide (NMA) frequency shifts using implicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 87 publications
2
56
0
Order By: Relevance
“…However, it should also be noted that such partitioning of the interaction potential and the frequency shift are approximate in nature, not only because the EFP description of the intermolecular interaction potential is an approximation but also because there could be artifacts introduced when thus obtained solvatochromic parameters are used for structurally distorted solute molecules in solutionsnote that, even though the original EFP method itself is based on rigid monomers, the vibrational solvatochromic calculation needs to consider structurally distorted molecules sampled from molecular dynamics simulation. The coarsegrained approach 9,33,34,42 has in this regard an important advantage because it already includes such structural distortion effects (see Refs. 33 and 34).…”
Section: B Solefp Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it should also be noted that such partitioning of the interaction potential and the frequency shift are approximate in nature, not only because the EFP description of the intermolecular interaction potential is an approximation but also because there could be artifacts introduced when thus obtained solvatochromic parameters are used for structurally distorted solute molecules in solutionsnote that, even though the original EFP method itself is based on rigid monomers, the vibrational solvatochromic calculation needs to consider structurally distorted molecules sampled from molecular dynamics simulation. The coarsegrained approach 9,33,34,42 has in this regard an important advantage because it already includes such structural distortion effects (see Refs. 33 and 34).…”
Section: B Solefp Methodsmentioning
confidence: 99%
“…In the previous works 2, 9,10,34,42 only the first summation terms in Eqs. (11) and (12) were taken into account because they were believed to be the dominant contributions.…”
Section: Electrostatic Interaction Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have suggested important contributions from dispersion, charge transfer, and polarisation effects. 64,66,67,[70][71][72][73] The electrostatic frequency mappings have been tested against ab initio calculations, 50,51,69,74 solvent experiments of single amide units, 52,60,73,75 gas phase experiments 76,77 of small peptides, and linear absorption of proteins. 62,64 So far, only one mapping for the amide unit preceding proline has been presented.…”
Section: Introductionmentioning
confidence: 99%